2004
DOI: 10.1088/0305-4470/37/42/r01
|View full text |Cite
|
Sign up to set email alerts
|

Perfect fluid theory and its extensions

Abstract: We review the canonical theory for perfect fluids, in Eulerian and Lagrangian formulations. The theory is related to a description of extended structures in higher dimensions. Internal symmetry and supersymmetry degrees of freedom are incorporated. Additional miscellaneous subjects that are covered include physical topics concerning quantization, as well as mathematical issues of volume preserving diffeomorphisms and representations of Chern-Simons terms (= vortex or magnetic helicity).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
256
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(262 citation statements)
references
References 98 publications
3
256
0
3
Order By: Relevance
“…There is indeed a natural framework for discussing the dynamics of fluids using intrinsic variables which has been used over the years to describe ideal fluid dynamics [33][34][35][36][37][38][39]. This framework was re-examined recently in [40] who suggested that it could be useful beyond the ideal fluid level; by studying the corrections to the ideal fluid effective action [41] argued that the transport of non-dissipative neutral fluids could be systematically understood in this framework.…”
Section: Jhep03(2014)034mentioning
confidence: 99%
“…There is indeed a natural framework for discussing the dynamics of fluids using intrinsic variables which has been used over the years to describe ideal fluid dynamics [33][34][35][36][37][38][39]. This framework was re-examined recently in [40] who suggested that it could be useful beyond the ideal fluid level; by studying the corrections to the ideal fluid effective action [41] argued that the transport of non-dissipative neutral fluids could be systematically understood in this framework.…”
Section: Jhep03(2014)034mentioning
confidence: 99%
“…This Hamiltonian supports two bands with the Bloch states |χ ± (k) , the nondegenerate energy eigenvalues 70) and the Berry curvatures…”
Section: Cmentioning
confidence: 69%
“…There could be other instances where such an Abelian treatment might fail. Examples of more sophisticated non-Abelian fluids were considered in several recent excellent reviews [84,85]. These papers might serve as points of departure for the treatment of more elaborate hydrodynamical problems involving non-Abelian entanglements.…”
Section: Miscellaneousmentioning
confidence: 99%